EFEKTIVITAS KERJA SAMA ASEAN DALAM MENGANTISIPASI TINDAK TERORISME - Fitri S, Syarmila Sofia (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
The ASEAN Convention on Counter Terrorism an the ASEAN Comprehensive Plan of Action on Counter Terrorism are the main instruments adopted to strengthen regional cooperation in facing the threat of terrorism. This study aims to determine the effectiveness of ASEAN cooperation through ACPoA-CT and to understand the development of terrorism in the Southeast Asian region as well as the implementation of ACPoA-CT by each ASEAN country. Using qualitative methods, the ACPoA-CT has succeede in strengthening cooperation in the areas intelligence sharing and deradicalization programs, especially in countries with better capacity such as Malaysia, Indonesia, and Singapore. The effectiveness of counter-terrorism cooperation is still limited due to the imbalance in the capacities of its member countries. Strengthened institutional and multilateral cooperation is needed to address the threat of terrorism in Southeast Asia. Research findings indicate that ACPoA-CT reflects profress in counter-terrorism cooperation in Southeast Asia, but has not yet achieved optimal effectiveness. Within the framework of multilateral cooperation, success is highly dependent on shared commitment and equality. More comprehensive policy improvements and harmonization are needed at the regional level to maintain effective sustainability. Keywords: ACPoA-CT, Effectiveness, Regional Cooperation, Terrorism.